2003
DOI: 10.1017/s1478951503030244
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation at end-of-life: The palliative care team's role

Abstract: This case highlights the observation that desire for hastened death fluctuates for patients at end-of-life and may be influenced by factors under the control of the palliative care team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Naturally, the desire for a hastened death depends on numerous factors. This desire may fluctuate over time (Goelitz, 2003) and may be influenced by interventions made by palliative care clinicians (Seale, 2010; Goelitz, 2003). As well, prior studies have revealed concerns about patients requesting a hastened death in order to avoid being a burden to others (Lee et al, 1996; Cavalieri et al, 2002) or when they felt familial, institutional, or social pressures (Battin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, the desire for a hastened death depends on numerous factors. This desire may fluctuate over time (Goelitz, 2003) and may be influenced by interventions made by palliative care clinicians (Seale, 2010; Goelitz, 2003). As well, prior studies have revealed concerns about patients requesting a hastened death in order to avoid being a burden to others (Lee et al, 1996; Cavalieri et al, 2002) or when they felt familial, institutional, or social pressures (Battin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A patient's desire to end one's life when anticipating or experiencing intolerable symptoms due to life-limiting illness is fundamentally different than using medications to alleviate pain that have the potential to accelerate death; in MAID, the intent is to end suffering by hastening death. While some scholars argue that robust palliative care can alleviate symptoms so effectively that MAID becomes unnecessary, 23 others argue that patients can experience such severe suffering from their illness that forcing them to continue living is contrary to the principle of nonmaleficence. 24 It is important to understand the legal requirements of each state's MAID laws and follow all institutional guidelines if prescribing medication with the intention of aiding a patient's death.…”
Section: Beneficence and Nonmaleficencementioning
confidence: 99%
“…Some patients with terminal illnesses have the desire for hastened death, and some request assisted suicide or exhibit signs of suicidal ideation (SI). 9 Suicidal ideation is correlated with psychiatric disorders that adversely affect the patient's emotional and psychological behaviour. 10 Patients with cancer have higher prevalence of psychiatric disorders.…”
Section: Evaluation and Treatment Of Patients With Suicidal Ideationmentioning
confidence: 99%